Characterization of the phenylalanine ammonia lyase gene from the rubber tree (Hevea brasiliensis Müll. Arg.) and differential response during Rigidoporus microporus infection - Sangsil Porntip; Nualsri Charassri; Woraathasin Natthakorn; Nakkanong Korakot (Journal of Plant Protection Research, 2016)
Phenylalanine ammonia lyase (PAL) is a specific branch point enzyme of primary and secondary metabolism. It plays a key role in plant development and defense mechanisms. Phenylalanine ammonia lyase from Hevea brasiliensis (HbPAL) presented a complete open reading frame (ORF) of 2,145 bp with 721 encoded amino acids. The sequence alignment indicated that the amino acid sequence of HbPAL shared a high identity with PAL genes found in other plants. Phylogenetic tree analysis indicated that HbPAL was more closely related to PALs in Manihot esculenta and Jatropha curcas than to those from other plants. Transcription pattern analysis indicated that HbPAL was constitutively expressed in all tissues examined, most highly in young leaves. The HbPAL gene was evaluated by quantitative real-time PCR (qRT-PCR) after infection with Rigidoporus microporus at 0, 12, 24, 48, 72 and 96 hours post inoculation. The expression patterns of the PAL gene differed among the three rubber clones used in the study. The transcription level of the white root rot disease tolerant clone, PB5/51 increased sharply during the latter stages of infection, while it was relatively subdued in the white root rot disease susceptible clones, RRIM600 and BPM24. These results suggest that the HbPAL gene may play a role in the molecular defense response of H. brasiliensis to pathogen attack and could be used as a selection criterion for disease tolerance.